Parental Effects on Epigenetic Programming in Gametes and Embryos of Dairy Cows - Wu, Chongyang; Sirard, Marc-André (Frontiers in Genetics, 2020)
The bovine represents an important agriculture species and dairy breeds have experienced intense genetic selection over the last decades. The selection of breeders focused initially on milk production, but now includes feed efficiency, health, and fertility, although these traits show lower heritability. The non-genetic paternal and maternal effects on the next generation represent a new research topic that is part of epigenetics. The evidence for embryo programming from both parents is increasing. Both oocytes and spermatozoa carry methylation marks, histones modifications, small RNAs, and chromatin state variations. These epigenetic modifications may remain active in the early zygote and influence the embryonic period and beyond. In this paper, we review parental non-genetic effects retained in gametes on early embryo development of dairy cows, with emphasis on parental age (around puberty), the metabolism of the mother at the time of conception and in vitro culture (IVC) conditions. In our recent findings, transcriptomic signatures and DNA methylation patterns of blastocysts and gametes originating from various parental and IVC conditions revealed surprisingly similar results. Embryos from all these experiments displayed a metabolic signature that could be described as an “economy” mode where protein synthesis is reduced, mitochondria are considered less functional. In the absence of any significant phenotype, these results indicated a possible similar adaptation of the embryo to younger parental age, post-partum metabolic status and IVC conditions mediated by epigenetic factors.